Enhancing Knowledge and Attitude Through mHealth App-Assisted Patient Education Among Elderly Patients with Uncontrolled Hypertension - Muhammad Thesa Ghozali; Fachri Argya Cahyadi; Satibi Satibi; Gerhard Fortwengel (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2025)
Hypertension remains a critical health challenge worldwide, with uncontrolled hypertension being a significant contributor to cardiovascular morbidity and mortality. Elderly patients often face difficulties in hypertension management due to limited knowledge, adherence barriers, and lack of education. This study aimed to evaluate the impact of an mHealth-assisted patient education intervention on knowledge and attitude among elderly patients with uncontrolled hypertension. A pre-experimental one-group pre-test and post-test design was conducted among 39 patients aged 46–55 years (48%) and 56-65 years (52%). Patients accessed an mHealth application featuring interactive hypertension management modules. Knowledge and attitude were assessed using validated questionnaires pre- and post-intervention. Results showed a significant improvement in both knowledge and attitude scores post-intervention (p 0.05). The mHealth-based approach effectively increased patient understanding and encouraged a positive attitude towards hypertension management. The study highlights the potential of mHealth applications in enhancing hypertension knowledge and attitude among elderly patients, emphasizing the need for integrating digital tools in routine hypertension care.